Dramaturgi Mahasiswa dan Mahasiswi Produktif Sosiologi Angkatan 2022 Universitas Jember pada Kehidupan Nyata dan Maya - Fierena Riza Guntari; Terry Franka Soenaryo; Fauziyah Almas Janani Widodo (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Students are individuals who are usually referred to as productive teenagers, because apart from playing their role as a student, they also play a productive role on campus. Where today's teenagers often play roles in the real world, especially when they play role plays in the virtual world. It is not enough for productive teenagers to only play roles on campus, they need experience outside campus. This research uses a qualitative method with a phenomenological approach, by understanding the phenomenon of productive students in the Sociology Study Program at the University of Jember. This research takes the perspective of dramaturgical theory put forward by Erving Goffman. Some students play roles in carrying out their activities in the real world and the virtual world. In this research, the conclusion was drawn that each student played a role play on the front stage and back stage.